The Effect of Alisher Navoy's Educational Ideas on the Spiritual and Moral Development of the Society - Ochilova Maftuna Shukhratovna- (Researchparks Publishing, 2023)
This article presents the philosophical views of Alisher Navoi. The spiritual and moral views of the thinker, which contribute to the development and progress of society, are reflected. Examples of his works are presented and analyzed.